Temperature sensing based on slow light via stimulated Brillouin scattering in M-shaped few-mode fiber - Li-Jun Li; Shang-Lin Hou (PLoS ONE, 2026)
This study investigates temperature sensing based on slow light generation via stimulated Brillouin scattering in an M-shaped few-mode fiber. The temperature-dependent properties of four optical modes (LP 01 , LP 11 , LP 21 , and LP 02 ) over a range from –20 °C to 80 °C are analyzed using the full-vectorial finite element method. Results show that the effective refractive index and Brillouin frequency shift of all modes increase with temperature, while the effective mode areas of all modes decrease. The LP 02 mode exhibits exceptional temperature sensitivity, showing a significant rise in slow light time delay from 0 ns to 514.9 ns, along with a growth in the pulse broadening factor. In contrast, the LP 01 mode maintains the largest time delay across the temperature range but shows less temperature-induced variation. The results demonstrate a trade-off between slow light enhancement (time delay) and signal distortion (pulse broadening). This study confirms that the LP 02 mode in the M-shaped few-mode fiber is highly suitable for developing sensitive fiber-optic temperature sensors, providing a theoretical foundation for optimizing slow light applications in sensing.